The Student-Self Oriented Learning Model as an Effective Paradigm for Education in Knowledge Society - Fomichov, Vladimir A.; Fomichova, Olga S. (Informatica, 2019)
Proceeding from broadly accepted role of emotional intelligence (EI) in professional and personal life, the paper suggests a new learning model (LM) called Student-Self Oriented LM (SSOL-model). It is defined as the model being beneficial for self-cognition and self-construction through the prism of the acquired knowledge and life experience. Two successful implementations of the SSOL-model are shortly described: the system of emotional-imaginative teaching (the EIT-system) developed by the authors in the 1990s and expanded in the 2000s and art cognitonics. The EIT-system is underpinned by the authors’ Theory of Dynamic Conceptual Mappings (the DCM-theory). The EIT-system includes an original method of developing figurative thinking and creativity at the lessons of second language (English for Russian children), literature and poetry in English and Russian, symbolic language of painting, and communication culture. It is stated that this method may be used as an effective starting framework of STEAM education. It is mentioned that the DCM-theory and the EIT-system became the starting point for developing the foundations of a new scientific discipline called cognitonics. The basic principles of art cognitonics – a well developed branch of cognitonics and the concept of cognitive engagement are described. The significance of art cognitonics for helping the learners to answer the encountered moral questions is explained. The broad possibilities of designing intelligent tutoring systems (ITSs) of new generation are indicated. These are culture and moral experience oriented systems aimed at developing figurative thinking, creativity, early socialization and helping the students to find in the outstanding art works the answers to emerging moral questions. An original, detailed script of an ITS contributing to early socialization of the learners is described, its literary source is the fairy-tale "Sleeping Beauty". Since the sphere of using the SSOL-model is not restricted, it is suggested to interpret this model as an effective paradigm for education in knowledge society and a strong support to anthropocentric approach to education in the digital age.